Sikap Moderasi Beragama mahasiswa di Universitas Jenderal Soedirman Purwokerto - Baedowi, Muhamad; Musmuallim; Riza Chamadi , Muhamad (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
This research aims to determine the religious moderation attitudes of students at Jenderal Soedirman University, Purwokerto. Students at these universities are very heterogeneous and come from various ethnicities, religions, and races, which makes it necessary to have a moderate attitude toward student activities that are religious in nature. This type of research is field research and qualitative descriptive research where data is taken through closed interview methods via Google Form surveys and observations. The results of this research are that the researchers obtained data that there were still 4.5% (27 students) who answered that there were campus organizations affiliated with radicalism and 95.5% (550 students) who responded that there were no organizations affiliated with radicalism. The researchers distributed a total of 576 respondents. Students participated in banned organizations in Indonesia. It turned out that three students (0.5%) answered that they followed, and 573 students (99.05%) did not participate. Students' perceptions regarding the existence of suicide bombings turned out that 0.5% (3 students) answered that they agreed with the presence of suicide bombings, and 99.05% (573 students) responded that they disagreed. So, students at Jenderal Soedirman University still need to increase their national insight and religious moderation to understand better the meaning of unity and difference within the nation and state.